2010
DOI: 10.1007/s00122-010-1406-6
|View full text |Cite
|
Sign up to set email alerts
|

Using probe genotypes to dissect QTL × environment interactions for grain yield components in winter wheat

Abstract: Yield is known to be a complex trait, the expression of which interacts strongly with environmental conditions. Understanding the genetic basis of these genotype × environment interactions, particularly under limited input levels, is a key objective when selecting wheat genotypes adapted to specific environments. Our principal objectives were thus: (1) to identify genomic regions [quantitative trait loci (QTL)] involving QTL × environment interactions (QEI) and (2) to develop a strategy to understand the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…QKh-2D.1 and QTw-2D might have been identified due to the presence of other linked genes. The Rht-B1 gene is associated with physiological processes that affect not only plant height but also yield, grain quality, seedling vigor and adaptability to adverse environments (Fischer and Stockman 1986;Gooding et al 1999Gooding et al , 2012McCartney et al 2006;Zheng et al 2010;Bai et al 2013;Zhang et al 2013;Asif et al 2015). This study indicated that Rht-B1b had negative effects on TKW, KW, KDR, TW, DT, and ZEL.…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 80%
“…QKh-2D.1 and QTw-2D might have been identified due to the presence of other linked genes. The Rht-B1 gene is associated with physiological processes that affect not only plant height but also yield, grain quality, seedling vigor and adaptability to adverse environments (Fischer and Stockman 1986;Gooding et al 1999Gooding et al , 2012McCartney et al 2006;Zheng et al 2010;Bai et al 2013;Zhang et al 2013;Asif et al 2015). This study indicated that Rht-B1b had negative effects on TKW, KW, KDR, TW, DT, and ZEL.…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 80%
“…QTL for GYS have been reported on almost all wheat chromosomes [1,33,35,36,37,38,39,40,41,42,43,44]. Most of these studies identified several grain yield QTL; however, the majority were detected in only single environments, and QTL detected in more than one environment showed considerable variation in magnitude of effect [1,36,37,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…QTL analyses to identify genomic regions associated with NUE have been conducted using both biparental recombinant inbred and doubled haploid populations from Asian and European germplasm in both seedling and full-season experiments Guo et al 2012;Sun et al 2013;Xu et al 2014;Laperche et al 2006Laperche et al , 2007Laperche et al , 2008Zheng et al 2010;Fontaine et al 2009;Habash et al 2007;Garcia-Suarez et al 2010;Bogard et al 2011bBogard et al , 2013. Association mapping (Bordes et al 2013;Cormier et al 2014) approaches also have been applied to NUE traits.…”
Section: Introductionmentioning
confidence: 99%